1H low field nuclear magnetic resonance relaxometry for probing biodiesel autoxidation. (1st August 2016) - Berman, Paula; Meiri, Nitzan; Linder, Charles; Wiesman, Zeev
Graphical abstract: Highlights: We study the oxidation stability of biodiesel and how it impairs fuel characteristics. New oxidative molecular structures affect physico-chemical properties of biodiesel. Oxidized products of biodiesel have different secondary interactions. Characterization of molecular interactions is a major application of 1 H LF-NMR relaxometry. Abstract: The oxidation stability of biodiesel composed of fatty acid esters derived from vegetable oils, is one of the major issues challenging its wide-spread use as an alternative fuel. The poor oxidative stability of biodiesel compared to petrodiesel, is due to its high content of unsaturated fatty acid methyl esters that negatively affects fuel properties such as storage lifetime. Moreover, the relationship between new molecules formed by oxidation and their new solution morphologies is a complex subject that affects physico-chemical properties of the fuel. The goal of this work was to understand how the oxidized unsaturated fatty acid methyl esters and the non-oxidized components of the biodiesel interact and affect the final properties of multi component biodiesel mixtures. Towards this objective standard pure fatty acid methyl esters and biodiesel mixtures were heated for different time periods with constant stirring to induce autoxidation, and then analyzed by 1 H low field nuclear magnetic resonance (LF-NMR) relaxometry. To further define the molecular consequence of autoxidation and appearance of autoxidation products, a combination of supporting methods, including, gas chromatography, Fourier transform infrared, 1 H high field NMR, and thermogravimetric analysis were used. 1 H LF-NMR relaxometry was proven to be an advantageous tool to study autoxidation of biodiesel. It is a direct, rapid, non-destructive method that can be used to study the underlying structural and compositional mechanisms that contribute to changes in the fuel's physico-chemical properties. For example we describe in this paper the interactive effect of new oxidative products and stable non-oxidized components upon each other's molecular movement and morphology during the process of oxidation. One major result was to show that the oxidized products of fatty acid methyl esters have different secondary interactions between themselves and the biodiesel components which were not oxidized but are mutually affected by each other. Characterizing these changes in molecular interactions and how they affect biodiesel properties is one of the major contributions of 1 H LF-NMR relaxometry. Also, the possibility of 1 H LF-NMR to analyze heterogeneous and at times heterophasic whole samples directly, including their physicochemical state, is of great value when studying the effect of different antioxidants on the oxidation stability of fuels and other food and biological systems.